1993
DOI: 10.1016/0735-1097(93)90230-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (3-month) effects of a new beta-blocker (nebivolol) on cardiac performance in dilated cardiomyopathy

Abstract: Nebivolol improved stroke volume, ejection fraction and left ventricular end-diastolic pressure, not through a measurable reduction in afterload or a lusitropic effect, but by improving systolic contractile performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1
7

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(56 citation statements)
references
References 24 publications
4
44
1
7
Order By: Relevance
“…The overall quality of the trials was high; each followed a double-blinded protocol, and only one study had possible irregularities in the randomization process (22). Follow-up of randomly assigned patients was almost complete.…”
Section: Resultsmentioning
confidence: 99%
“…The overall quality of the trials was high; each followed a double-blinded protocol, and only one study had possible irregularities in the randomization process (22). Follow-up of randomly assigned patients was almost complete.…”
Section: Resultsmentioning
confidence: 99%
“…39 Labetalol has not been systematically investigated in heart failure populations but has been shown to improve myocardial function in subjects with hypertensive cardiomyopathy. 40 Another third-generation compound with limited but favorable experience 41,42 in heart failure trials is nebivolol, which is a markedly ␤ 1 -selective 43 compound whose vasodilatory action appears to be due to potentiation of nitric oxide. 44 Two other ␤-blockers with vasodilating activity, carvedilol and bucindolol, have been extensively evaluated in the treatment of chronic heart failure.…”
Section: Three Classes Of ␤-Blockers Available For Clinical Usementioning
confidence: 99%
“…47,56,58 However, some data also demonstrate no difference between a second-and third-generation compound. 59 Both second-and third-generation compounds improve intrinsic systolic function, 41,60,61 and prevent deterioration in function and progression in remodeling, [62][63][64][65][66] and reverse remodeling. 63,66 As discussed below, from a clinical standpoint it would appear that both second-and thirdgeneration compounds reduce hospitalizations and mortality, but quantitative differences in clinical responses may exist.…”
Section: Three Classes Of ␤-Blockers Available For Clinical Usementioning
confidence: 99%
“…The increase of CFR might also indicate an improvement of coronary microvascular dysfunction, responsible of microvascular angina pectoris or silent ischemia in patients without epicardial artery stenosis (32). The improvement of coronary microvessel function could be even one of the mechanisms sustaining the improvement of LV function demonstrated by both carvedilol and nebivolol (33)(34)(35)(36)(37)(38)(39)(40). Sugioka and coworkers (17) observed that CFVR improvement after carvedilol was greater in patients with LV ejection fraction increase ≥ 10% (1.3 ± 0.6) than in those with election fraction increase < 10% (0.4 ± 0.5) (p<0.01).…”
Section: Third Generation Beta-blockers (With Vasodilating Action) Anmentioning
confidence: 99%